KOLABORASI PENTAHELIX DALAM MEWUJUDKAN SATUAN PENDIDIKAN AMAN BENCANA (SPAB) PADA TK AISYIYAH DI KOTA MEDAN - Harfiani, Rizka; Mavianti, Mavianti (Yayasan Rahmat Islamiyah, 2024)
This article is the result of ResearchMu's Community Service (CSA) activities which aim to create a Disaster Safe Education Unit (DSEU) at the Aisyiyah Bustanul Athfal (ABA) Kindergarten level in Medan City. The realization of DSEU is one of the work programs of this CSA partner, namely the Environmental and Disaster Management Institute (EDMI) for the Regional Leadership of 'Aisyiyah, North Sumatra Province. This CSA program includes three activities, namely; 1) Environmental and disaster education activities, targeting school residents who are parents of ABA Kindergarten students; 2) Providing assistance with disaster equipment and infrastructure to DSEU project schools, namely kindergartens. ABA 05 Kindergarten Dadap Village, Medan, and 3) Conducted DSEU Training of Trainers (TOT) for school principals and ABA Kindergarten teachers throughout Medan City. The strategy used in implementing CSA is a collaboration of pentahelix elements, namely: 1) The government makes the policy, in this case BNPB and BPBD; 2) The partner organization is EDMI for the Regional Leadership of 'Aisyiyah, North Sumatra Province, which collaborates with Muhammadiyah Disaster Management Centre for the Regional Leadership of Muhammadiyah North Sumatra; Early Childhood, Primary and Secondary Education CouncilÂ of Medan City, and ABA Teachers Association of Medan City; 3) Academics who are resource persons are lecturers according to their field of expertise and; 4) The target community for activity participants is school residents, school principals, teachers and student guardians, as well as 5) Print and electronic media, which propagates this good practice activity. The result of this CSA is the realization of DSEU which has become a project school, as well as an increase in the understanding of ABA kindergarten school residents throughout the city of Medan about disaster education which is correlated with improving the quality of early childhood education.